2009
DOI: 10.1097/ss.0b013e3181a396ba
|View full text |Cite
|
Sign up to set email alerts
|

Soil Developmental Stages of Layered Cambisols and Calcisols on Socotra Island, Yemen

Abstract: Semiarid tropical regions are very suitable to study the polygenesis of layered substrates and soils. To determine relic and recent soil features of tropical soils, pedons in the northern part of Socotra Island, Yemen, were investigated. The aim of the study was to create developmental stages of widely distributed soils, which in particular are layered Cambisols and Calcisols. In most layers of those investigated soils, denudative components occur, which clearly indicate the relocation of coverloams and coverc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Periodically sayls may have brought sufficient water to support the development of a weak soil mainly represented by partial decalcification with corresponding ironhydroxide precipitation and residual clay enrichment, well known from other dry tropical areas (Khormali et al, 2003;Pietsch and Kü hn, 2009). Since soil formation also modified the sediment filling of the fireplace (Bwkb horizons) to the same degree as the adjacent buried land surface, some time must have passed before the area around the fire place was irrigated.…”
Section: Neolithic Fireplace Soil Formation and The Beginning Of Sabmentioning
confidence: 99%
“…Periodically sayls may have brought sufficient water to support the development of a weak soil mainly represented by partial decalcification with corresponding ironhydroxide precipitation and residual clay enrichment, well known from other dry tropical areas (Khormali et al, 2003;Pietsch and Kü hn, 2009). Since soil formation also modified the sediment filling of the fireplace (Bwkb horizons) to the same degree as the adjacent buried land surface, some time must have passed before the area around the fire place was irrigated.…”
Section: Neolithic Fireplace Soil Formation and The Beginning Of Sabmentioning
confidence: 99%
“…Soil and climate change research in Yemen conducted in recent years has highlighted these drastic climatic changes Geoderma 185-186 (2012) [48][49][50][51][52][53][54][55][56][57][58][59][60] in Southern Arabia (e.g. Fleitmann et al, 2007;Lézine et al, 2007;Parker et al, 2006;Pietsch and Kühn, 2009;Sirocko et al, 1993;Wilkinson, 2005). Few studies of afforestation, a very important strategy for soil protection and for combating soil erosion, have been reported in Yemen.…”
Section: Introductionmentioning
confidence: 99%
“…Argillic horizons in calcareous soils of arid to semiarid regions characterized by limited leaching may indicate periods of more humid climatic conditions in the past. Pietsch and Kuhn (2009) reported that calcium carbonate found at a depth of up to 30 cm in most of the layered soils is very typical of an increasing aridity in parts of the semiarid tropics, particularly in areas with high groundwater levels and interflow.…”
Section: Introductionmentioning
confidence: 98%